Extracorporeal membrane oxygenation for acute respiratory distress syndrome in adults: an analysis of differences between survivors and non-survivors. (September 2017) - Panholzer, Bernd; Meckelburg, Katrin; Huenges, Katharina; Hoffmann, Grischa; von der Brelie, Michael; Haake, Nils; Pilarczyk, Kevin; Cremer, Jochen; Haneya, Assad
Objectives: Over the last decade, extracorporeal membrane oxygenation (ECMO) has become a promising option for patients with severe acute respiratory distress syndrome (ARDS). In this single-center observational cohort study, data from a patient group with severe ARDS treated with ECMO was analyzed. Methods: Data from 46 patients [median age 54 years (18 to 72), male: 65.2%] were evaluated retrospectively between January 2009 and September 2015. Results: Diagnosis leading to ARDS was pneumonia in 63.1% of the patients. The median SOFA Score was 13 (10 to 19) and the median LIS was 3.5 (2.67 to 4). The median duration of ECMO support was 12 days (1 to 86). Twenty-eight patients (60.9%) were successfully weaned from ECMO and 22 patients survived (47.8%). Non-survivors needed significantly more frequent renal replacement therapy (37.5% vs. 18.2%; p<0.01) and transfusion of red blood cell concentrates [0.4 units (0.3 to 1.2) vs. 0.9 units (0.5 to 1.6); p<0.01] during ECMO support compared to patients who survived. Conclusion: This report suggests that ECMO currently allows treatment of severe ARDS with presumed improved survival. The incidence rate of acute kidney injury and transfusion are associated with adverse outcomes.